ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENERIMAAN PAJAK (Studi Empirik di Kantor Pelayanan Pajak Pratama Surakarta) - Cahyono, Yuli Tri (Universitas Muhammadiyah Surakarta, 2017)
This research is aimed to examine and analyze the influence of tax evasion, tax compliance by tax payer, self assessment system, awareness of tax payer, the comprehension on tax laws, and perceptions of service quality towards the level of tax income. The total sample of this research were 95 individual tax payers. The technique to collect sample in this research is convenience sampling. The data analysis method is multiple linear regression. The results of this research shows that the variable of perceptions of service quality give the influence towards the tax income, meanwhile the variable of tax evasion, tax compliance by tax payer, self assessment system, awareness of tax payer, the comprehension on tax laws are not influence towards the tax income.Â Keywords: tax evasion, self assessment system, perceptions of service quality, the level of tax incomeÂ